Ultrasound criteria for assessing the correction of metabolic-associated fatty liver disease and liver blood flow disorders using arginine in patients with coronary artery disease in combination with COVID-19 - S.Ye. Mostovyi; M.M. Zhaivoronok; O.M. Safonova (Gastroenterologìa)
Background. Coronavirus disease 2019 (COVID-19) remains one of the most urgent global health problems today. In the conditions of its spread around the world, the global scientific community is trying to study not only respiratory, but also extrapulmonary manifestations of this infection. It is known that with COVID-19, the endothelium, the hemostasis system, and the liver are affected with the occurrence of such a complication as metabolic dysfunction-associated steatotic liver disease (MASLD). The most vulnerable group of patients in terms of coronavirus disease and its complications (including MASLD) are those with coronary heart disease (CAD), therefore the search for effective drugs and optimal ultrasound criteria to evaluate liver steatosis in the dynamics of treatment is the main task of modern medicine. Goal: to determine the ultrasound criteria for assessing the correction of MASLD and liver blood flow disorders using arginine in patients with CAD associated with COVID-19. Materials and methods. A prospective study was conducted in 52 patients with CAD combined with PCR-positive COVID-19. The study was carried out upon admission to the hospital and 6 months after discharge. Group I (n = 27) consisted of CAD + COVID-19 patients who, in addition to standard therapy for MASLD, received arginine for 6 months after discharge from the hospital; group II (comparison group, n = 25) included participants who received standard therapy without arginine. Results. Splanchnic artery duplex scanning at baseline showed that 21 (78.0 %) patients in group I and 19 (76.0 %) in group II had a decrease in peak systolic velocity (PSV) in the proper hepatic artery (PHA), an increase in portal vein blood flow at the beginning of treatment, as well as increased liver size in 20 (74.0 %) patients in group I and 17 (68.0 %) in group II. An increase in the attenuation coefficient was detected in all patients of groups I and II. There were no differences between the groups at the time of inclusion in the study in terms of splanchnic blood flow and attenuation coefficient. After 6 months of arginine treatment, an improvement in the portal vein blood flow and a decrease in blood flow velocity in the PHA, a decrease in the diameter of the portal vein, a decrease in the size of the right and left liver lobes were found in group I, with no improvement in group II. A repeated study revealed a decrease in the attenuation coefficient in group I and no changes in group II. At the beginning of the study, a direct correlation was found between fibrinogen and the attenuation coefficient in group I (r = 0.54; p < 0.05), as well as in group II (r = 0.51; p < 0.05). After 6 months, C-reactive protein decreased in both groups. Conclusions. In patients with CAD combined with COVID-19 in the presence of MASLD, a decrease in the portal vein blood flow and an increase in PSV in the PHA were found. When arginine was used for 6 months in combination with standard therapy, according to the European Society of Cardiology protocols, there was a significant decrease in the attenuation coefficient, PSV in the PHA, and an increase in the portal vein blood flow. This indicates the possibility of using the attenuation coefficient as the main marker, and PSV in the PHA and the portal vein blood flow as additional criteria for ultrasound assessment of MASLD correction with arginine in patients with CAD combined with COVID-19.